The Analysis of Code-Switching in Travel Vlogs on the Youtube Channel of Alman Mulyana - Windi Chaldun; Z. Zulfan; Fadillah Shela Putri; P. Pujiati; Kacar Ginting (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2026)
This study examines the phenomenon of Arabic–Indonesian code-switching in the travel vlogs of Alman Mulyana on YouTube. The study is motivated by the gexcerpt ing use of digital platforms as spaces where multilingual practices naturally occur. A qualitative descriptive method was employed, and excerpt were purposively selected from 11 vlogs containing clear instances of code-switching. The vlogs are accessible through the link https://www.youtube.com/@AlmanMulyana1983. The excerpt were analyzed using the equivalent method to identify both the types and causal factors of code-switching. The results reveal three types: inter-sentential (60%), intra-sentential (30%), and tag switching (10%). In terms of factors, the most dominant is the intention of clarifying the speech content for the interlocutor (70%), followed by repetition for clarification (15%), while interjection and expressing group identity each account for 5%. The conclusion of this research is that code-switching in Alman Mulyana’s vlogs is used communicatively for Arabic native speakers and Indonesian audiences, and the dominance of inter-sentential code-switching indicates that Alman’s proficiency in Arabic is quite good, allowing him to use it almost on par with his first language. Code-switching in Alman’s vlogs functions primarily as a communicative strategy rather than a stylistic choice. The study contributes to sociolinguistic research by presenting YouTube as an authentic site of bilingual practice.